Evaluating EAP Textbooks for Indonesian University Students Using Impressionistic and In-depth Assessment - Imroatus Solikhah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study was qualitative content analysis that evaluated the quality of English for University Teaching (EUT), English for Specific Purposes (ESP), and English for Academic Purposes (EAP) textbooks through impressionistic and in-depth analysis. The participants were 9 EAP teachers and 15 EAP students from three universities in Surakarta, Indonesia. Instruments to collect data were checklist and interview guide. The checklist consisted of impressionistic analysis to see (1) cover, (2) content scope, (3) learning activities, (4) book organization, and (5) layout; and the in-depth analysis, namely (1) aim and approach, (2) organization design, language and content, (3) language skills, and (4) practical consideration. Data were collected using checklist and Focus Group Discussion. Data were analyzed through summative content analysis with seven stages: transforming data into narrative text, determining unit of analysis, developing categories, coding, coding the entire text, checking consistency of coding, and drawing conclusion. Results show EUT and ESP have low quality based on the impressionistic evaluation, and fair quality of their in-depth evaluation. Both books are register and grammar oriented. EAP textbook is good in general, and very good in depth. EAP presents its contents in terms of genre reading, academic speaking, academic reading, academic writing and grammar.